A physiologically based pharmacokinetic/pharmacodynamic model to determine dosage regimens and withdrawal intervals of aditoprim against Streptococcus suis - Mi, Kun; Sun, Lei; Zhang, Lan; Tang, Aoran; Tian, Xiaoyuan; Hou, Yixuan; Sun, Lingling; Huang, Lingli (Frontiers in Pharmacology, 2024)
Streptococcus suis (S.suis) is a zoonotic pathogen threatening public health. Aditoprim (ADP), a novel veterinary medicine, exhibits an antibacterial effect against S.suis. In this study, a physiologically based pharmacokinetic/pharmacodynamic (PBPK/PD) model was used to determine the dosage regimens of ADP against S.suis and withdrawal intervals. The PBPK model of ADP injection can predict drug concentrations in plasma, liver, kidney, muscle, and fat. A semimechanistic pharmacodynamic (PD) model, including susceptible subpopulation and resistant subpopulation, is successfully developed by a nonlinear mixed effect model to evaluate antibacterial effects. An integrated PBPK/PD model is conducted to predict the time-course of bacterial count change and resistance development under different ADP dosages. ADP injection, administrated at 20 mg/kg with 12 intervals in consecutive 3 days, can exert an excellent antibacterial effect while avoiding resistance emergence. The withdrawal interval at the recommended dosage regimen is determined as 18 days to ensure food safety. This study suggests PBPK/PD model can be applied as an effective tool for the antibacterial effect and safety evaluation of novel veterinary drugs.